2020
DOI: 10.1016/j.drugalcdep.2019.107725
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of monetary reward in amygdala, insula, caudate are predictors of pleasure sensitivity to d-Amphetamine administration

Abstract: Background-Drug addiction and dependence continue as an unresolved source of morbidity and mortality. Two approaches to identifying risk for abuse and addiction are psychopharmacological challenge studies and neuroimaging experiments. The present study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 87 publications
2
8
0
Order By: Relevance
“…Consistent with this hypothesis, we recently showed that greater activation in mesolimbic reward regions to monetary reward anticipation in a drug-free state was associated with greater subjective rewarding effects of acute d-amphetamine [51,52]. Using a design similar to the one described here, healthy young adults participated in behavioral sessions in which they received amphetamine and placebo, followed by a drug-free imaging session to assess neural response to monetary reward.…”
Section: Introductionsupporting
confidence: 62%
“…Consistent with this hypothesis, we recently showed that greater activation in mesolimbic reward regions to monetary reward anticipation in a drug-free state was associated with greater subjective rewarding effects of acute d-amphetamine [51,52]. Using a design similar to the one described here, healthy young adults participated in behavioral sessions in which they received amphetamine and placebo, followed by a drug-free imaging session to assess neural response to monetary reward.…”
Section: Introductionsupporting
confidence: 62%
“…43 Furthermore, activation of insula and striatum during reward-based tasks are associated with liking of amphetamine. 44 Here, we show that DA activity is altered in these regions following amphetamine intake, with the exception for medial temporal lobe. The absence of occupancy change in medial temporal lobe was partly surprising given significant amphetamine-induced DA level elevations in past microdialysis work.…”
Section: Discussionmentioning
confidence: 55%
“…The MeA also showed significant resting state connectivity throughout the insula. Nearly all subregions of the amygdala are reciprocally connected with the insula (Mufson et al, 1981 ) and amygdala-insula connections are thought to govern disgust, appetite, reward, and satiety (Sarinopoulos et al, 2006 ; Boutelle et al, 2015 ; Langenecker et al, 2020 ). Further research is needed to understand whether extensive connectivity between the MeA and the insula represents an olfactory function.…”
Section: Discussionmentioning
confidence: 99%
“…The resting state connectivity map of the CoA included the caudate and substantia nigra, both of which have been shown to exhibit connectivity with the amygdala, as components of a well-studied limbic anticipatory-reward circuit (Lee et al, 2006 ; Langenecker et al, 2020 ). The CoA also showed significant resting state connectivity with the periaqueductal gray (PAG) area, which is involved in respiratory control and motivated behaviors (Motta et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%